Invisible Minority: Military-Connected Adolescents in Secondary Schools - Hanna, Jennie (My University, 2018)
Military families and military-connected children are a vital source of support – the backbone for soldiers fighting in our armed forces. There are currently four million military-connected children in the U.S. and 80% of them attend public schools. Schools can play a key role in helping to support military-connected adolescents, yet this group remains unacknowledged. Even though many students are part of this invisible minority, little is known about how military-connected adolescents view themselves and their experiences as part of the military culture. The purpose of this study is the better understand the life of military-connected adolescents to help inform teaching and learning in secondary schools. Narrative inquiry works to restory a participant’s life by gathering, analyzing, and rewriting data in a sequence that makes sense, and searching for themes. Co-constructed narratives were developed for each of nine participants. Themes that emerged reveal the invisible lives of these military-connected adolescents. Themes include confidence, empathy, maturity, and adaptability. Military-connected adolescents experience life on the move, new schools, being the new kid on the block, repeatedly saying goodbye, and (hopefully) reunification. Military-connected adolescents respond through a series of different coping strategies as they struggle to make sense of military life. Implications and recommendations for findings include 1) identifying military-connected adolescents in secondary schools, 2) including information on military culture as a part of pre-service teaching and professional development for educators, 3) supporting military-connected adolescents in schools; and 4) reinforcing resiliency.
Keywords: Education, Secondary.; Military Studies.; Education, Educational Psychology.; Education, General.